The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.12.01.470853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Evolutionary Dynamics of Hyperparasites

Abstract: Evolutionary theory has typically focused on pairwise interactions, such as those between hosts and parasites, with relatively little work on more complex interactions including hyperparasites: parasites of parasites. Hyperparasites are common in nature, with the chestnut blight fungus virus CHV-1 a well-known natural example, but also notably include the phages of important human bacterial diseases. Theory on hyperparasitism has mostly focused on their impact on the evolution of virulence of their parasite ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our study is closely related to previous theoretical explorations of evolution in host-parasitehyperparasite systems (Sandhu et al 2021;Northrup et al 2021). Sandhu et al (2021) also explored the evolution of parasite virulence, but in contrast to our study found that the introduction of a hyperparasite generally selects for increased virulence and reduces the average mortality rate of the host.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Our study is closely related to previous theoretical explorations of evolution in host-parasitehyperparasite systems (Sandhu et al 2021;Northrup et al 2021). Sandhu et al (2021) also explored the evolution of parasite virulence, but in contrast to our study found that the introduction of a hyperparasite generally selects for increased virulence and reduces the average mortality rate of the host.…”
Section: Discussionsupporting
confidence: 70%
“…We focused our investigation on the evolution of virulence, but the evolutionary dynamics of the hyperparasite are also likely to be important (Sandhu et al 2021; Northrup et al 2021). However, in certain cases the hyperparasite might behave as if it is evolutionarily static (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations